2022
DOI: 10.1371/journal.pone.0276249
|View full text |Cite
|
Sign up to set email alerts
|

The associations between autistic traits and disordered eating/drive for muscularity are independent of anxiety and depression in females but not males

Abstract: Previous research has shown a positive correlation between autistic traits and eating disorder symptoms, and this relationship appears to be independent of co-occurring mental health status. The current study followed a pre-registered analysis plan with the aim to investigate a previously unconsidered factor in the relationship between autistic traits and disorders of eating and body image: the drive for muscularity. Participants (N = 1068) completed the Autism Spectrum Quotient (AQ), Hospital Anxiety and Depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
0
3
1
Order By: Relevance
“…Unlike autistic traits overall, which were only related to eating disorder psychopathology for the female sub-sample, difficulty with attention switching was related to increased eating disorder psychopathology in both females and males. In comparison to the few studies that have evaluated the role of biological sex in this domain, the relationship between autistic traits and eating disorder psychopathology has previously been reported as being stronger among females [ 49 , 66 ], a finding which was not replicated by the present study. Taking these findings together, it is logical to suggest that even sub-clinically, autistic traits contribute to the presence of eating disorder psychopathology, and that this might be more salient among females [ 53 , 67 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike autistic traits overall, which were only related to eating disorder psychopathology for the female sub-sample, difficulty with attention switching was related to increased eating disorder psychopathology in both females and males. In comparison to the few studies that have evaluated the role of biological sex in this domain, the relationship between autistic traits and eating disorder psychopathology has previously been reported as being stronger among females [ 49 , 66 ], a finding which was not replicated by the present study. Taking these findings together, it is logical to suggest that even sub-clinically, autistic traits contribute to the presence of eating disorder psychopathology, and that this might be more salient among females [ 53 , 67 ].…”
Section: Discussioncontrasting
confidence: 99%
“…While mental health history is an important consideration for future research in this, or any other field related to mental health, one study reported that a correlation between eating disorder psychopathology and autistic traits exists independent of traits related to anxiety and depression [ 49 ]. Another found that this was only true for female participants [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 8 studies, three were cross-sectional (Galvin et al, 2022;Krumm et al, 2017;Mansour et al, 2016), one experimental (Kuroki & Fukui, 2020), and four qualitative (Brede et al, 2020;Healy et al, 2021;Jachyra et al, 2019;Walker et al, 2020). Publication dates ranged from November 2016 to October 2022.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…It was therefore concluded that difficulties with emotional dysregulation may play a role in increased body dissatisfaction among autistic individuals. Second, Galvin et al (2022) examined the mediating role of the drive for muscularity between autistic traits and ED pathology among a neurotypical sample (n = 1068, M age = 28.65 years). Authors identified a significant positive correlation between Drive for Muscularity Scale (i.e., one's desire to have a more muscular body; McCreary & Sasse, 2000) total scores (r = 0.077, p < 0.05) and muscle-oriented body image subscale scores (r = 0.125, p < 0.001) and AQ total scores.…”
Section: The Relationship Between Body Image and Autismmentioning
confidence: 99%